2005
DOI: 10.14411/eje.2005.030
|View full text |Cite
|
Sign up to set email alerts
|

Mate choice and reproductive success of two morphs of the seven spotted ladybird, Coccinella septempunctata (Coleoptera: Coccinellidae)

Abstract: Abstract. Mate choice, reproductive success and fecundity of typical and melanic morphs of C. septempunctata were studied. Melanic as well as typical individuals preferred to mate with melanic males and females. Mate choice was mainly determined by females and to a lesser degree by males. Mating duration, oviposition period, and lifetime fecundity were highest (51.20 ± 2.82 min, 47.00 ± 2.79 days and 705.40 ± 69.85 eggs) when a melanic female mated with a melanic male and lowest (38.94 ± 1.68 min, 26.10 ± 2.54… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…Also, multiple studies on pre-and post-copulatory sexual selection have been conducted on this ladybird. Ladybird beetles are known to show non-random mate preferences based on morph (Saeki et al, 2005;Srivastava and Omkar, 2005;Bista and Omkar, 2015), size (Brown, 1990a, b), food conditions (Ueno et al, 1998;Dubey, 2016) and age (Pervez et al, 2004;Srivastava and Omkar, 2004;Omkar and Singh, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Also, multiple studies on pre-and post-copulatory sexual selection have been conducted on this ladybird. Ladybird beetles are known to show non-random mate preferences based on morph (Saeki et al, 2005;Srivastava and Omkar, 2005;Bista and Omkar, 2015), size (Brown, 1990a, b), food conditions (Ueno et al, 1998;Dubey, 2016) and age (Pervez et al, 2004;Srivastava and Omkar, 2004;Omkar and Singh, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Bezzerides et al (2007) showed that alkaloids concentrations in H. axyridis were negatively correlated with the size and intensity of melanic spots, particularly in females, and concluded that non-melanics were better chemically defended. Srivastava and Omkar (2005) studied a melanic morph of Coccinella septempunctata L. and found that melanism was associated with increased longevity, fecundity, and mate preference in this species, despite the relative rarity of melanics in the field. Srivastava and Omkar (2005) studied a melanic morph of Coccinella septempunctata L. and found that melanism was associated with increased longevity, fecundity, and mate preference in this species, despite the relative rarity of melanics in the field.…”
Section: Introductionmentioning
confidence: 99%
“…True (2003) discussed insect melanism in the context of other life history traits, and suggested molecular mechanisms operating at the level of either gene regulation or protein coding could lead to pleiotropic effects on other traits with important biological functions. Srivastava and Omkar (2005) studied a melanic morph of Coccinella septempunctata L. and found that melanism was associated with increased longevity, fecundity, and mate preference in this species, despite the relative rarity of melanics in the field. Similarly, Berkvens et al (2007) measured differences in performance between melanic and succinic phenotypes of H. axyridis , and concluded that the latter had greater nutritional plasticity.…”
Section: Introductionmentioning
confidence: 99%
“…Data for other species indicate that variation in color, such as melanic morphs in Coccinella septempunctata (L.) and Menochilus sexmaculatus (Fabricius), is associated with faster development of immatures and greater fecundity and longevity of adults (Srivastava & Omkar, 2005;Dubey et al, 2016). Under similar conditions and prey availability in the field, yellow individuals of C. externa could behave similar to green ones, but other differences associated with abiotic and biotic factors that influence the field performance, such as dispersal ability or protective camouflage, cannot be ruled out.…”
Section: Discussionmentioning
confidence: 99%
“…Under similar conditions and prey availability in the field, yellow individuals of C. externa could behave similar to green ones, but other differences associated with abiotic and biotic factors that influence the field performance, such as dispersal ability or protective camouflage, cannot be ruled out. Data for other species indicate that variation in color, such as melanic morphs in Coccinella septempunctata (L.) and Menochilus sexmaculatus (Fabricius), is associated with faster development of immatures and greater fecundity and longevity of adults (Srivastava & Omkar, 2005;Dubey et al, 2016). On the other hand, melanic morphs of Chrysomela lapponica (L.) and Helicoverpa armigera (H€ ubner) exhibited lower fecundity compared to individuals of standard color (Ma et al, 2008;Zverev et al, 2018).…”
Section: Discussionmentioning
confidence: 99%